Rescuing psychoanalytic tragedy from ideological romanticism: Book review Richards, B (1989) Images of Freud: Cultural responses to psychoanalysis. London: JM Dent & Sons - ISBN 0460024906. - Ivey, Gavin (PINS-Psychology in Society, 2025)
Since its inception a century ago psychoanalysis has radically transformed our collective psychological life, in spite of the fact that very few people have undergone psychoanalytic treatment. This is testimony, not only to the impact of intellectual theory on a culture's self-understanding, but also to the specific mode of critical self-awareness with which Freud infected contemporary first-world society. No area of our cultural life, whether it be literature, art, film, education or history has escaped the psychoanalytic influence. Like it or not, we work, love and dream in Freud's shadow even though few of us have lain on his couch. Given this fact, one might assume that the way in which Freud's ideas have been received and interpreted by the discipline of psychology would provide us with insight into contemporary psychology's own unconscious and, by extension the unconscious of modern cu1ture generally. It is this thesis which informs Barry Richards' latest book, Images of Freud.